Using social media and web 2.0 technology for business continuity - White, Connie (Henry Stewart Talks, 2011)
What are social networks?, Characteristics of disasters, Challenges in information, What can social media do for you?, Facebook, Live streaming, Connect, Subscribing is the link, Message notification, Going viral, Some social media concepts, Familiarize yourself with what's available, Searching for information, Hashtags, Twitter, Provide links, Videos, Warning and preparedness, Cross-promoting, Keep media attention, Group support, Blogs, Privacy settings, Mapping, Aggregating social identities, Skype, Leveraging social media, Phases and information flow
Archived at 2022/04/26